Do Thin Capitalization, Return on Asset, and Company Size Impact Tax Avoidance? Empirical Evidence from Transportation and Logistics Companies - Oktiani, Riska; Zainuddin, Muhammad Fandy; `Ulayya, Afira Nida (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
This study aims to determine the impact of thin capitalization, return on asset, and company size on tax avoidance, specifically among publicly listed companies in the transportation and logistics sector from 2019 to 2022. The research encompasses all data from companies listed on the Indonesia Stock Exchange within this sector. Considering the available data, a total of 60 samples were selected as the objects of this study. The testing method employed was multiple linear regression analysis using panel data. This research distinguishes itself by addressing a critical gap in existing literature on tax avoidance, shedding light on previously unexplored sector and presenting novel insights into the interplay between thin capitalization, return on assets, company size and tax avoidance in the transportation and logistics industry. Our multiple linear regression analysis concludes that thin capitalization and return on asset have inverse relation with tax avoidance, meanwhile, company size has a positive relation to tax avoidance. We also discover that return on assets partially has influence on tax avoidance, whereas thin capitalization, return on asset and company size simultaneously influence tax avoidance.